PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN DESA WISATA DAN IMPLIKASINYA TERHADAP KETAHANAN SOSIAL BUDAYA (STUDI DI DESA WISATA BRAYUT PANDOWOHARJO KEC. SLEMAN KAB. SLEMAN D.I. YOGYAKARTA) - , Anggun Hendryantoro ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this research is defining the realization of community empowerment through the development of tourism village, describing the problems arisen in its process, and its implications related to the villageâs sociocultural resilience. The research use descriptive-qualitative method and the technique employed in collecting data is observation, indepth interview, library research, and documentation. The object of the research and the main source of data is a village called Desa WisataBrayut (the tourism village of Brayut). This village is selected using purposive sampling technique. The research has led to the finding that the process of empowering community through the development of DusunBrayut in Pandowoharjo, Sleman as a tourism village consists of three stages. The first stage is the socialization of tourism village concept and the benefits of the concept implementation to the people of DusunBrayut, the inventory of the villageâs potentials as a tourism object and the identification of chances to build community participation in the village. The second stage is the process of capability transformation where interventions from the stakeholders is aimed at enhancing community empowerment process through a fund aid program called PNPM Mandiri Pariwisata (The National Program for Community Empowerment Mandiriin Tourism) and through human resources training and development. In the third step, the DusunBrayut as a tourism village is achieving its self-sufficiency in performing tourism management through its ability in conducting self-promotion, creating its own tourism market, and facilitating touristsâ visits whenever required. In sum, a successful community empowerment is achieved when Desa Wisata Brayutâs management is capable of organizing Brayut peopleâs participation in planning, operating, and evaluating as well as in conducting continuous monitoring on the tourism village. In result, empowering community through the development of tourism village as implemented in DusunBrayut has strengthened the villageâs sociocultural security in terms of community institutions, communal responsibilities, religious tolerance, social sanctions, art and culture preservation, traditions, and lifestyle.